Methods of identity defence – slava and litiya - Todorović, Ivica (Sociološki pregled, 2025)
The text presents the current manifestations of the most significant and influential Serbian folk rituals (Slava and Litiyа), which connect Christian and folk traditions. Some of their new expressions are especially important nowadays, when they have once again found themselves at the centre of the defence against attempts to deconstruct Serbian identity. The paper is primarily based on the research of Litiyа events (the so-called “Litiyа uprisings”) in the past few years, as well as on years-long studies of new ideas about the origin of Serbian clans, determined by family Slava. Due to their importance, Litiyа and Slava were often banned precisely as essential Serbian identity features. The latest events have fully confirmed their status in modern circumstances.